2022
DOI: 10.1038/s41380-022-01619-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in HIV-associated depression: evidence and future perspectives

Abstract: People living with HIV face a high risk of mental illness, especially depression. We do not yet know the precise neurobiological mechanisms underlying HIV-associated depression. Depression severity in the general population has been linked to acute and chronic markers of systemic inflammation. Given the associations between depression and peripheral inflammation, and since HIV infection in the brain elicits a neuroinflammatory response, it is possible that neuroinflammation contributes to the high prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 231 publications
(226 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the development of HIV-associated neuroinflammation and cognitive impairment has been directly linked to gut dysbiosis and increased intestinal permeability [ 127 ]. It has been proposed that HIV-induced alterations in the balance of neurotransmitters in the brain contributes to disruption of the gut–brain axis, which can lead to the development of depression and other neuropsychiatric symptoms [ 128 ].…”
Section: Role Of Host Microbiota In Susceptibility To Viral Infection...mentioning
confidence: 99%
“…Furthermore, the development of HIV-associated neuroinflammation and cognitive impairment has been directly linked to gut dysbiosis and increased intestinal permeability [ 127 ]. It has been proposed that HIV-induced alterations in the balance of neurotransmitters in the brain contributes to disruption of the gut–brain axis, which can lead to the development of depression and other neuropsychiatric symptoms [ 128 ].…”
Section: Role Of Host Microbiota In Susceptibility To Viral Infection...mentioning
confidence: 99%
“…Other recent work has shown that monocyte-associated cerebrospinal fluid (CSF) biomarkers, such as TNF-α, MCP-1, neopterin, soluble CD14, and neurofilament light chain protein (NFL), are strongly associated with neuronal damage in people both with and without HIV-1 [ 17 , 18 ]. Furthermore, other authors [ 18 , 19 ] have discussed the use of brain tissue, CSF, and blood biopsies to assess glial cell activation or elevated cytokines, as well as the use of tissue samples to indirectly measure neuroinflammation. Indeed, some pro-inflammatory markers present in CSF have been used as indicators of neuroinflammation, given that CSF is directly connected both to the brain [ 19 ], inflammatory cytokines, and interleukin-15 (IL-15) [ 19 ].…”
Section: Important Genes Involved In the Development Of Hiv-associate...mentioning
confidence: 99%
“…This directly challenges the 95-95-95 goals defined by UNAIDS; 95% of PLWH should know their status, 95% of PLWH who know their status should be on ART treatment, and 95% of PLWH on treatment should be virally suppressed by 2025 [29,30]. The burden of mental health disorders experienced by PLWH can partly be explained by several factors such as discrimination [31,32] and HIV-related inflammation [33][34][35]. Furthermore, some studies suggest that certain ART drugs such as efavirenz may play a role in developing depression, but without uniform evidence [36][37][38].…”
Section: Introductionmentioning
confidence: 99%